2004
DOI: 10.1063/1.1642278
|View full text |Cite
|
Sign up to set email alerts
|

Secondary ion mass spectrometry for the identification of polymers with noncharacteristic secondary ions using multivariate statistical analysis

Abstract: Eleven different, filler-free polymers were depth profiled until all secondary ion signals were stable. Discriminant function analysis and principal components analysis were performed on a dataset containing the intensities of noncharacteristic hydrocarbon secondary ions, measured in this steady state. Discriminant function analysis showed that these secondary ions were sufficient to correctly identify all polymers using leave-one-out correction. Even with principal components analysis, which uses no prior kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…They observed that at higher irradiation doses cross-linking is dominant and at low irradiation doses chain scission dominates. Multvariate statistical analysis was used to demonstrate that 11 polymers could be identified from databases containing noncharacteristic secondary ions measured under steady-state SIMS conditions (98). Van Gennip et al showed that all 11 polymers could be identified using principle component analysis (98).…”
Section: Secondary Ion Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that at higher irradiation doses cross-linking is dominant and at low irradiation doses chain scission dominates. Multvariate statistical analysis was used to demonstrate that 11 polymers could be identified from databases containing noncharacteristic secondary ions measured under steady-state SIMS conditions (98). Van Gennip et al showed that all 11 polymers could be identified using principle component analysis (98).…”
Section: Secondary Ion Mass Spectrometrymentioning
confidence: 99%
“…Multvariate statistical analysis was used to demonstrate that 11 polymers could be identified from databases containing noncharacteristic secondary ions measured under steady-state SIMS conditions (98). Van Gennip et al showed that all 11 polymers could be identified using principle component analysis (98). Segalman et al used dynamic SIMS to measure the diffusion of deuterium-labeled atactic PS from the surface of a polydisperse isotactic PS (99).…”
Section: Secondary Ion Mass Spectrometrymentioning
confidence: 99%